2022
DOI: 10.1093/jxb/erac045
|View full text |Cite
|
Sign up to set email alerts
|

Can we improve the chilling tolerance of maize photosynthesis through breeding?

Abstract: Chilling tolerance is necessary for crops to thrive in temperate regions where cold snaps and lower baseline temperatures place limits on life processes; this is particularly true for crops of tropical origin such as maize. Photosynthesis is often adversely affected by chilling stress, yet the maintenance of photosynthesis is essential for healthy growth and development, and most crucially for yield. In this review we describe the physiological basis for enhancing chilling tolerance of photosynthesis in maize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 128 publications
2
15
0
Order By: Relevance
“…Chilling stress damages photosystems in maize [ 17 ]; we provide evidence that photosynthesis proteins drop much earlier than previously reported in maize. Previous studies showed that photosynthetic light-reaction proteins decreased after long durations of cold treatment [ 17 ], such as 12 h of cold treatment at 4 °C [ 54 ].…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Chilling stress damages photosystems in maize [ 17 ]; we provide evidence that photosynthesis proteins drop much earlier than previously reported in maize. Previous studies showed that photosynthetic light-reaction proteins decreased after long durations of cold treatment [ 17 ], such as 12 h of cold treatment at 4 °C [ 54 ].…”
Section: Discussionsupporting
confidence: 52%
“…Much progress has been made in understanding the physiological response of cold stress in maize [ 1 , 3 , 17 ], but the genetic basis of the cold adaptation in maize remains poorly characterized [ 1 , 3 , 17 , 18 ]. Physiological and genetic studies suggest that chilling temperatures affect distinct metabolic functions at different maize growth stages, each under the control of independent gene sets [ 1 , 17 ]. Temperatures below 10 °C negatively affect gemination rate and slow seedling establishment [ 1 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… Posch et al (2022) show that thermal tolerance of PSII in wheat is subject to rapid acclimation in response to short-term supraoptimal temperature conditions, but also varies significantly between a range of genotypes with contrasting high temperature tolerance. Finally, on the suboptimal end of growth season temperature, Burnett and Kromdijk (2022) argue the case for enhancing chilling tolerance of photosynthesis in maize via selective breeding, which may help to better adapt the global number one grain crop to its increasingly temperate surroundings as its cultivation area spreads further north.…”
Section: Leveraging Natural Genetic Variation In Photosynthesis To Im...mentioning
confidence: 99%